กองทุนคุ้มครองผู้เอาประกันชีวิต - รัฐยา ผานิชชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
Life insurance companies are classified as a type of financial institutions, collecting the different kind of savings from the others, called "a premium". In case of life insurance companies encounter the financial problems, life Insurance Act B.E.2535 does not have any regulation in the assured’s protection from getting the sum insured back according to life insurance contract. In this case it is different from the bank deposit insurance system. This research is aimed to investigate the regulations in protection from damages and to ensure the assured to enter into a life insurance contract.The findings, studying from the foreign laws, find that the establishment of the assured’s protection fund is a method to prevent the assured against the financial problems of life insurance companies. As a results, the researcher suggests that it should establish the assured’s protection fund in Thailand. And this fund should have the same characteristics as bank deposit insurance corporation.